COVID-19: mortality, future years lost, and demographic structure : Italy and Kenya compared - Bell, Clive (Working paper, 2020)
COVID-19 causes extremely high mortality among the old. This motivates a comparison of the losses of future lifetime years and future lifetime years of work ensuing from a hypothetical 25,000 excess deaths in Italy, whose affluent population is one of the world's oldest, with those in Kenya, whose population is one of the most youthful and poor. If Italy's excess mortality profile were scaled up three-fold and then came to pass in Kenya, the aggregate loss of future lifetime working years would be slightly higher than Italy's, whereas the aggregate number of deaths and the loss of future lifetime years would be only about one third of Italy's-with all aggregate losses scaleable. Italy's profile implies a loss of 9.9 years of expected future life for each death and 1.8 years of expected working life, both scale-invariant within wide limits. For Kenya, the corresponding estimates are 14.0 and 8.2 years. Vaccines and debt relief apart, these findings suggest that donors might do better to concentrate on the old enemies malaria, HIV/AIDS, and diseases of childhood.